2021
DOI: 10.3389/fimmu.2021.669747
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TLR4 Signaling Impedes Tumor Growth in Colitis-Associated Colon Cancer

Abstract: Patients suffering from ulcerative colitis are at increased risk of developing colorectal cancer. Although the exact underlying mechanisms of inflammation-associated carcinogenesis remain unknown, the intestinal microbiota as well as pathogenic bacteria are discussed as contributors to inflammation and colitis-associated colon cancer (CAC). In the present study, we analyzed the impact of TLR4, the receptor for Gram-negative bacteria derived lipopolysaccharides, on intestinal inflammation and tumorigenesis in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 52 publications
0
21
0
1
Order By: Relevance
“…Ultimately, microbiota-driven IL-17C induces the expression of Bcl-2 and Bcl-xl in IECs to improve IECs survival and promote cancer development [ 98 ]. In line with this, TAK-242 (a small-molecule TLR4 inhibitor) strongly suppressed the development and progression of colonic tumors during DSS-induced colitis, with reduced numbers of infiltrating macrophages and colonic proinflammatory cytokine levels [ 99 ]. Moreover, for APC Min/+ MyD88 -/- mice, both mortality and tumor numbers were dramatically decreased [ 100 ].…”
Section: Mechanisms Of Colorectal Cancer In Ulcerative Colitismentioning
confidence: 96%
“…Ultimately, microbiota-driven IL-17C induces the expression of Bcl-2 and Bcl-xl in IECs to improve IECs survival and promote cancer development [ 98 ]. In line with this, TAK-242 (a small-molecule TLR4 inhibitor) strongly suppressed the development and progression of colonic tumors during DSS-induced colitis, with reduced numbers of infiltrating macrophages and colonic proinflammatory cytokine levels [ 99 ]. Moreover, for APC Min/+ MyD88 -/- mice, both mortality and tumor numbers were dramatically decreased [ 100 ].…”
Section: Mechanisms Of Colorectal Cancer In Ulcerative Colitismentioning
confidence: 96%
“…They observed that by inhibiting TLR4 with an antagonist during intestinal inflammation, the development and progression of colonic tumours was significantly reduced compared to control mice [ 30 ]. They also observed a decrease in infiltration of pro-inflammatory cells and cytokines compared to control mice [ 30 ]. CPT-11 prevented tumour growth equally well in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…It can modulate both innate and adaptive immune responses through multiple pathways and mechanisms [ 29 ]. Apart from being present on immune cells, it is expressed by many tumors including skin malignancies [ 9 , 10 , 11 , 12 , 13 , 16 , 17 ]. TLR4 expression has been found to be higher in cutaneous SCCs than in normal skin [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptors are not only expressed on the cells of the immune system but are also expressed on tumor cells, where they may influence tumor growth and host immune [ 8 ]. Depending on the tumor type and/or the initiating agent, TLR4 ligation in the tumor microenvironment may have the beneficial effect of activating anti-tumor responses or the deleterious action of promoting non-specific inflammatory responses [ 9 , 10 , 11 , 12 , 13 ]. Polymorphisms in the TLR4 allele in humans have been linked to the cancer susceptibility and resistance, depending on the type of cancer studied.…”
Section: Introductionmentioning
confidence: 99%